(untitled) (East West Medical College Journal, 2026)
Introduction: Liver cirrhosis and chronic liver disease (CLD) is the global burden of disease. In Bangladesh, liver disease has increased over the last few decades. The trends of morbidity and mortality from liver disease have increased considerably. Spontaneous bacterial peritonitis (SBP) is one of the common and life-threatening complications of patients with cirrhotic ascites. Factors associated with the risk of developing SBP in cirrhotic patients include upper gastrointestinal bleeding, poor liver function, low ascitic fluid protein levels, prior SBP and hospitalization. Assessing the prevalence and risk factors of spontaneous bacterial peritonitis (SBP) is pivotal for proper treatment, prognosis in patients of liver cirrhosis for reducing the mortality and morbidity. Materials and Methods: This study was a cross sectional observational study, conducted at Shaheed Suhrawardy Medical College Hospital, over a consecutive 6-month period. Samples were selected by purposive sampling technique. Sample size was 50. Detail demographic data were collected from the patients and recorded in structured case. report form. Clinical examination and relevant investigation were done meticulously. All collected questionnaire checked very carefully to identify the error in the data. Data processing work consist of registration schedules, editing computerization, preparation of dummy table, analyzing and matching of data Result: In this study maximum number of patients 22(44.0%) were between 31-45 years of age group, mean age of the patient was 37.05 ± 9.32 years. Large numbers of respondents came from urban area 32(64.0), followed by rural area 18(36.0%). Among the patients, poor class 24(48%) comprises the major percentage of the patients. Out of 50 cases 34(68.0%) of patients were male and 16(32.0%) were female. Male – female ratio was 2.1:1. Abdominal distension was the commonest presentation (100%), followed by jaundice (82%), vague abdominal pain (76%), vomiting (44%) and haematemesis 18%. Among the all clinical sign, ascites (100%) were commonest sign, followed by icterus (86%) and loss of body hair 60%. Maximum number of CLD patients was Child’s B class 27(54.0%). Followed by 11(22.0%) of patients Child’s C class and 12(24.0%) of patients Child’s A class. Mean values serum bilirubin of the study population was 2.83 ± 1.52 (mg/dl), serum albumin was 24.90 ± 4.08 (gm/L), ALT was 45.94 ± 24.64 (IU/L), AST was 50.89 ± 30.18 (IU/L), INR was 1.52 ± 0.29. Present study demonstrated that prevalence of SBP was 13(26.0%) in cirrhotic patients. Among this, 9 cases were CPNA, 4 cases were CNNA. None of the case detected MNB. Predisposing factor revealed that low total protein level (61.5%), Child–Pugh class C (61.5%) and Sepsis (46.1%) were significant factors for SBP. The difference between groups was statistically significance (p<0.05). Conclusion: Spontaneous bacterial peritonitis (SBP) is a common complication encountered in patients with liver cirrhosis. Present study demonstrated that prevalence of SBP was 13(26.0%) in cirrhosis patients. Early detection and appropriate management of spontaneous bacterial peritonitis is a pivotal in patients with liver cirrhosis for reducing the mortality and morbidity. EWMCJ Vol. 14, No. 1, January 2026: 26-35